Design of output feedback proportional–integral controller for polynomial fuzzy systems - Radmanesh, Hamid Reza; Moarefianpour, Ali; Jahed‐Motlagh, Mohammad Reza (Asian journal of control, 2023)
In this paper, the design of dynamic output feedback control law for polynomial fuzzy systems is studied. The main purpose is to design a tracker control law for fuzzy polynomial systems that are subject to external bounded disturbances. The structure of the control law is considered as fuzzy proportional–integral control. The conditions for deriving the control law are formulated in the form of a sum of square (SOS) feasibility problem. The designed control law will be able to force the system state vector to follow the state vector of a stable reference model in addition to guaranteeing the H∞ performance measure. The simulation results show the efficiency of the proposed method exposed to external disturbance.